Resources for phylogenomic analyses of Australian terrestrial vertebrates. (25th November 2016) - Bragg, Jason G.; Potter, Sally; Bi, Ke; Catullo, Renee; Donnellan, Stephen C.; Eldridge, Mark D. B.; Joseph, Leo; Keogh, J. Scott; Oliver, Paul; Rowe, Kevin C.; Moritz, Craig
Abstract: High‐throughput sequencing methods promise to improve our ability to infer the evolutionary histories of lineages and to delimit species. These are exciting prospects for the study of Australian vertebrates, a group comprised of many globally unique lineages with a long history of isolation. The evolutionary relationships within many of these lineages have been difficult to resolve with small numbers of loci, and we now know that many lineages also exhibit substantial cryptic diversity. Here, we present a set of phylogenetically diverse transcriptome resources to enable exon‐based sequence capture studies of Australian vertebrates, including transcriptome sequences for four species of birds, four frogs, seven lizards and seven mammals. We also use exon data from the marsupial transcriptomes we generated to examine an approach for choosing a moderate number (dozens or hundreds) of phylogenetically informative exons based on a single transcriptome sequence, and a relatively distant reference genome.